Keterbatasan Ruang Penyimpanan Protokol Notaris Pada Majelis Pengawas Daerah - Widiarista, I Putu Putra; Dewi, Anak Agung Istri Atu (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024), 2024)
This research aims to determine the storage arrangements for notary protocols that are 25 years old or more at MPD and to analyze alternative forms of storing notary protocols by the MPD. To examine this issue, this analysis was carried out using a normative legal research method with a statutory approach and a conceptual approach through collecting legal materials which were then analyzed descriptively. Based on the analysis carried out, it was concluded that the MPD is obliged to accept notarial protocols if at the time of handing over the protocol to the notary receiving the protocol has reached the age of 25 years or older. However, this provision cannot yet be implemented because MPD has limited or even full storage space. To overcome this problem, the alternative that can be taken is through efforts to store notarial protocols electronically and determine the expiration period for notarial deeds and other protocols.